2014
DOI: 10.5296/ijafr.v4i2.6586
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Factors Affecting Usage and Adoption of Internet & Mobile Banking In Pakistan

Abstract: Evolution of technology is a swift process, however, its acceptance and adoption in the society is slackened despite its promising results. Internet / mobile banking is a technological way of conducting banking transactions. The purpose of the current study is to find out the affect of various factors effecting successful adoption of internet   / mobile banking using TAM, technological acceptance model in Pakistan, especially rural areas of the country. Results of the current study obtained using regression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 49 publications
3
23
0
5
Order By: Relevance
“…This trust may mean trust in technology, trust in service, or trust in service providers (Nawaz & Yamin, 2018). Many researches studied people's trust in the technology acceptance model (Abu-Shanab & Ghaleb, 2012;Gao, et al, 2014;Maduku, 2014;Mazhar, et al, 2014). According to Lee and Song (2013), it concluded that trust positively influenced both performance expectancy and effort expectancy.…”
Section: Trustmentioning
confidence: 99%
“…This trust may mean trust in technology, trust in service, or trust in service providers (Nawaz & Yamin, 2018). Many researches studied people's trust in the technology acceptance model (Abu-Shanab & Ghaleb, 2012;Gao, et al, 2014;Maduku, 2014;Mazhar, et al, 2014). According to Lee and Song (2013), it concluded that trust positively influenced both performance expectancy and effort expectancy.…”
Section: Trustmentioning
confidence: 99%
“…Extant studies of Hanafizadeh et al (2014), Luarn and Lin (2005), and Wang and Liao (2007) have found significant positive impact of PEOU on customers' attitude toward acceptance of and loyalty to m banking. Mazhar et al (2014) concluded that PEOU is a major attribute in electronic channels of banking and commerce. Recent studies have ascertained that PEOU is a highly influential factor in adoption of mobile commerce (Liébana-Cabanillas et al, 2017), online banking (Al-Somali et al, 2009), mobile payments (C. Kim et al, 2010), and mobile shopping (Ko et al, 2009).…”
Section: Core Barriersmentioning
confidence: 99%
“…That e-government systems will improve customer execution and productivity supported by a gigantic effect between perceived usefulness on attitudes [30]. The results that perceived usefulness emphatically influenced a person's attitudein the use of flexible banking and web banking [25]. In perspective on the depiction, the going with theories are proposed: H2: Perceived usefulness affects the attitude of customers Consumer intentions can be impacted by attitude, the states of [14] that there is a positive impact among attitude and behavioral intention to utilize versatile banking in Malaysia.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…That e-government frameworks will improve client execution and efficiency bolstered by a huge impact between perceived usefulness on attitudes [24]. Besides discovered outcomes that perceived usefulness positively affected an person attitude in using mobile banking and web banking [25].…”
Section: Introductionmentioning
confidence: 99%